2022
DOI: 10.1007/s43678-022-00422-w
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study comparing outcomes before and after the introduction of an intubation protocol during the COVID-19 pandemic

Abstract: Objective Orotracheal intubation is a life-saving procedure commonly performed in the Intensive Care unit and Emergency Department as a part of emergency airway management. Prior to the COVID-19 pandemic, our center undertook a prospective observational study to characterize emergency intubation performed in the emergency department and critical care settings at Manitoba’s largest tertiary hospital. During this study, a natural experiment emerged when a standardized “COVID-Protected Rapid Sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Thirdly, the high VL usage rate may have contributed to the sustained FPS levels. Multivariate analysis showed that VL was independently significantly associated with FPS, and several other studies have supported the relationship between high VL use and high FPS [15,20,25,27,30]. In addition, VLs have a clear advantage over DLs in the donning of PPE [25,36].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Thirdly, the high VL usage rate may have contributed to the sustained FPS levels. Multivariate analysis showed that VL was independently significantly associated with FPS, and several other studies have supported the relationship between high VL use and high FPS [15,20,25,27,30]. In addition, VLs have a clear advantage over DLs in the donning of PPE [25,36].…”
Section: Discussionmentioning
confidence: 69%
“…Multivariate analysis showed that VL was independently significantly associated with FPS, and several other studies have supported the relationship between high VL use and high FPS [15,20,25,27,30]. In addition, VLs have a clear advantage over DLs in the donning of PPE [25,36]. Although portable VLs with smaller screens were used significantly more during the pandemic period, the OR for FPS was not different from that for mounted VLs with larger screens (OR 2.12 vs. 2.16).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The impact of intubator experience may have played a role in the high rate of first-pass success observed (as many position statements recommended the most experienced available provider perform intubations) but this variable was not available in the CCEDRRN registry. Studies comparing pre- and post-COVID-19 intubation practices found intubator experience to be positively associated with first-pass success [ 22 ]. First-pass success is an operational surrogate for patient outcomes [ 23 ], with multiple intubation attempts having been associated with increased adverse events and complications [ 4 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can help identify patients who are more likely to experience clinical deterioration and who require close supervision, early transfer for critical care, or other timely interventions. Thus, the use of MEWS in medical emergency units might be a helpful tool to enhance patient care, guarantee optimal resource utilisation, and avoid neglecting or improperly discharging unwell patients 8 The National Early Warning Score outperformed the other scores in predicting ICU admission, while the Modified Early Warning Score outperformed the other severity levels in predicting hospital mortality 9. Modified early warning scoring systems may be used in emergency rooms to anticipate patient clinical outcomes at the time of the initial examination and can also be a useful tool for determining the patients' prognosis 10 This study was conducted to assess and associate the Modified Early Warning Score (MEWS) in predicting critical care unit admission among patient in emergency department.…”
Section: Introductionmentioning
confidence: 99%